Group Work Practice Principles for Substance Use Disorder Treatment - Kelly, Brian L; Konyakova, Olga (Groupwork, 2019)
In this group work in practice essay, the authors review the theories, perspectives, and themes of group work practice specific to the SUD treatment field. Through a discussion of abstinence-based and harm reduction approaches to SUD treatment, a review of the types of groups used in SUD treatment and related group facilitation skills, and practice examples, the authors present important principles in the teaching and practice of group work in the SUD treatment field. While the authors’ experience is grounded in a U.S.-based context, we believe the principles presented are useful to a larger, international audience.